2021
DOI: 10.1103/physrevlett.126.028103
|View full text |Cite
|
Sign up to set email alerts
|

Swirling Instability of the Microtubule Cytoskeleton

Abstract: In the cellular phenomena of cytoplasmic streaming, molecular motors carrying cargo along a network of microtubules entrain the surrounding fluid. The piconewton forces produced by individual motors are sufficient to deform long microtubules, as are the collective fluid flows generated by many moving motors. Studies of streaming during oocyte development in the fruit fly Drosophila melanogaster have shown a transition from a spatially disordered cytoskeleton, supporting flows with only s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…3 d, indicates fluid speeds from zero to 0.15 μm/s, comparable to velocities observed during cytoplasmic streaming, e.g., ref. 45 . Interestingly, the sharpest gradients in the fluid velocity are found near the edges of the droplets (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…3 d, indicates fluid speeds from zero to 0.15 μm/s, comparable to velocities observed during cytoplasmic streaming, e.g., ref. 45 . Interestingly, the sharpest gradients in the fluid velocity are found near the edges of the droplets (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoscale motor proteins, such as kinesin and dynein, convert the cell's chemical energy source, adenosine triphosphate (ATP), into mechanical energy and effectively "walk" along the MT in a processive motion from one end of the MT to the other (1,15,16). Kinesin motor proteins are $60 nm in size and take 8-nm steps in a stochastic, processive motion to transport cargos (i.e., lipid vesicles or organelles) by acting individually or in groups (17)(18)(19). These out-of-equilibrium cellular mechanisms have provided inspiration for a variety of novel in vitro experiments in recent years and biopolymers with molecular motors have been used to create some of the first examples of molecular-scale active phases.…”
mentioning
confidence: 99%
“…A cytoskeletal vortex has not previously been described within any prokaryotes as far as we know. In eukaryotes, a vortex of cytoplasmic motion dependent on microtubules and actin has been shown to be critical for development by driving cytoplasmic streaming in the eggs of several species as well as in plant cells (Schroeder and Battaglia, 1985;Serbus et al, 2005;Stein et al, 2021;Woodhouse and Goldstein, 2013). The eukaryotic cytoskeleton is responsible for the rotation of the nucleus to align with cell polarity in motile cells, particularly fibroblasts (Fruleux and Hawkins, 2016;Gerashchenko et al, 2009;Kim et al, 2014;Levy and Holzbaur, 2008;Maninová et al, 2014;Wu et al, 2011) and has been observed in a vortex-like arrangement during misalignment (Kumar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%